E-Report: Holistic Assessment System in Elementary School - Widiana, I Wayan (Universitas Pendidikan Ganesha, 2021)
A good learning is supported by not only good planning and learning processes, but it is also supported by an assessment of students’ competencies achievement. This study aims to develop a learning outcome assessment system based on educational units (students’ reports) in elementary schools. This is development research using Development and Diffusion (R-D-D) model. The data in this study were collected through interviews, observations, questionnaires, documentation studies, FGDs, and product trials. The data were analyzed using a qualitative approach. The results showed that the percentage level of achievement of the unit-based learning outcomes assessment system was 97.3% so which fell into Very Good qualification with the achievement level scale of 5 in the conversion table. Based on this, it can be concluded that the Student Report (SR) system is appropriate to be used as an education unit-based learning outcome assessment system in elementary school. This research implies that teachers can use the developed E-report as a learning outcomes assessment system based on education units in elementary schools.